Joint exposure to multiple air pollutants and residual cardiovascular risk in hypertension - Yalan Li; Wei Hong; Jingjing Wu; Jie Wang; Shiqi Liu; Hong Yuan; Jingjing Cai; Rujia Miao; Jiangang Wang; Yao Lu (Ecotoxicology and Environmental Safety)
Background: Despite the widespread availability of antihypertensive medications, residual cardiovascular risk of hypertension remained high. Limited studies have investigated the link between air pollution, particularly joint exposure to multiple air pollutants, with residual cardiovascular risk of hypertension. Methods: 1981 hypertensive patients (≥ 18 years) from an ongoing longitudinal cohort in China, were enrolled between 2013 and 2019. Using high-quality datasets from China, the ground-level air pollutants concentrations, including PM2.5, PM2.5–10, SO2, O3, CO and NO2, at each participant’s residence were calculated. The relationships between individual and multiple air pollutants with the residual cardiovascular risk were assessed by Cox proportional hazards models, air pollution score analyses and Bayesian Kernel Machine Regression model. Results: Over an average follow-up period of 2.24 years (SD, 1.25), 706 hypertensive patients developed cardiovascular disease. In the single-pollutant analysis, higher concentrations of PM2.5, PM2.5–10, SO2 and CO were linked to increased residual cardiovascular risk. The air pollution score analyses and Bayesian kernel machine regression suggested that combined exposure to multiple air pollutants had a positive association with the residual cardiovascular risk, and NO2 played a dominant role. With higher NO2 concentrations, the hazard ratio of individual pollutants to residual cardiovascular risk increased. Conclusions: Prolonged exposure to a mixture of various air pollutants is linked to elevated residual cardiovascular risk in individuals with hypertension. Apart from taking antihypertensive medication and adopting healthy lifestyle behaviors, hypertensive patients should lower air pollutant exposure to decrease residual cardiovascular risk.